(untitled) (Journal of Philosophy Culture and Political Science, 2018)
“Idols” are obstacles in the way. scientific knowledge that were called Francis Bacon "ghosts." Logical the basis of the emergence of such "idols" is the most elementary form of human thinking flowed in the form of simple attributive judgments. The need to save such ghosts in modern society already has a psychology sociopolitical, idiological and economic foundations.